Correlation between cerebral blood flow and olfactory function in mild cognitive impairment and Alzheimer's disease. (10th March 2021) - Kashibayashi, Tetsuo; Takahashi, Ryuichi; Fujita, Jun; Fujito, Ryoko; Kamimura, Naoto; Okutani, Fumino; Kazui, Hiroaki
Abstract: Objective: Olfactory dysfunction is common in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD). We sought to elucidate brain regions associated with olfactory dysfunction in patients with MCI and early AD by using 123I‐IMP‐SPECT to detect regional cerebral blood flow (CBF). Methods: We included 218 patients diagnosed with AD or MCI, who underwent a comprehensive battery of neuropsychiatric and neuropsychological tests, Alzheimer's Disease Assessment Scale‐Cognitive Part (ADAS‐Cog), and forward‐ and backward‐digit span. Olfactory function was assessed using T&T olfactometry of five odors; patients stated whether they experienced any smell (detection test) and identified the odor (identification test). The association between single‐photon emission computerized tomography based regional CBF and olfactory function was examined by voxel‐by‐voxel multiple regression analysis, considering sex, age, and education as covariate parameters. Results: Of the 218 patients, 78 had mildly impaired olfactory detection and 15 had olfactory detection loss; additionally, 213 had mild olfactory identification impairment. The odor detection score correlated significantly with the ADAS‐Cog word recall score ( r = 0.193, p = 0.004). The odor identification score correlated significantly with the ADAS memory (r = 0.408, p < 0.001) and ADAS orientation ( r = 0.292, p < 0.001) scores. The odor identification score correlated negatively with CBF in the left temporal pole, entorhinal area, and bilateral frontal poles ( p < 0.001). Conclusion: Olfactory identification dysfunction in patients with MCI and AD is attributable to reduced CBF of the left temporal pole, entorhinal area, and bilateral frontal pole. Key points: Olfactory dysfunction is frequently observed in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD) Single‐photon emission computerized tomography (SPECT) might enable us to elucidate the association between sites of early damage in patients with MCI or AD, undetectable by magnetic resonance imaging (MRI) and olfactory dysfunction We determined the brain regions responsible for olfaction by using 123I‐IMP‐SPECT to detect regional cerebral blood flow (CBF) in patients with MCI and early AD The present study found that odor identification was associated with the bilateral frontal pole, in addition to the left temporal pole and entorhinal area, which had been identified in the previous studies using MRI Odor identification impairment was present in 97.7% of MCI/early AD patients Odor detection scores correlated significantly with the ADAS‐Cog word recall scores Odor identification correlated significantly with Mini‐Mental State Examination (MMSE), memory, and orientation Odor identification but not odor detection correlated negatively with CBF The left temporal pole, entorhinal area, and bilateral frontal poles are involved